The time of Stalin : portrait of a tyranny - Antonov-Ovseyenko, Anton; Saunders, George; Cohen, Stephen F. (New York : Harper & Row, 1983)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Stalin, Jozef; Sovjet-Unie.